El concepto de clásico y su aplicación a la literatura española = The concept of the classic and its application to Spanish literature - Carrera, Antonio (Lectura y signo, 2020)
En este trabajo se ofrece una reflexión sobre el concepto de lo clásico, siguiendo las consideraciones y argumentos de algunos célebres críticos como María Rosa Lida y, en especial, T. S. Eliot, y su aplicación a la Literatura española. This paper offers a reflection on the concept of the classic, following the considerations and arguments of some famous critics such as María Rosa Lida and, specially, T. S. Eliot, and its application to Spanish Literature.